Grain growth in soft magnetic ferritic stainless steels under compressive stresses at high temperatures. Issue 1 (March 2021) - Suzuki, S.; Onuki, Y.; Uchida, M.; Sato, S.; Naruse, T.; Watanabe, M.; Sato, T.; Ebata, T.
Abstract: Precipitation-hardened ferritic stainless steels are used for soft magnetic actuators of engines, as these steels exhibit high strength and soft magnetic properties. These ferritic stainless steels are hardened by nanoscale precipitates formed during an aging process after solution treatment. Furthermore, texture control of these steels is required in order to improve the soft magnetic properties. Therefore, texture control of ferritic stainless steels with <100> fiber texture by deformation at high temperatures is attempted in this study, as it has been demonstrated that the texture of ferritic Fe-Si alloys is significantly changed by deformation conditions, including temperature and strain rate. The results demonstrate that grains with the <100> fiber texture in the present stainless steels are preferentially evolved by compressive deformation under specific strain rates at high temperatures.